Laser irradiation of WE54 surface through simulated body fluid layer - Khadka, Indira (2019)
Magnesium and its alloys are promising biomaterials for temporary implant application because of their degradability and biocompatibility [1,2]. The surface morphology, micro-structure, and chemical composition of material are vital for cell adhesion. In this study, laser treatment of WE54 in simulated body fluid (SBF) has been carried out to explore the technique to produce bio-structures through various ion deposition such as Ca/P on WE54 surface so as to improve its surface bio-functionality.